NICER uncovers the transient nature of the type-B quasi-periodic oscillation in the black hole candidate MAXI J1348−630. Issue 3 (31st May 2021) - Zhang, L; Altamirano, D; Uttley, P; García, F; Méndez, M; Homan, J; Steiner, J F; Alabarta, K; Buisson, D J K; Remillard, R A; Gendreau, K C; Arzoumanian, Z; et al.
ABSTRACT: We present a systematic spectral-timing analysis of a fast appearance/disappearance of a type-B quasi-periodic oscillation (QPO), observed in four Neutron Star Interior Composition Explorer ( NICER ) observations of MAXI J1348−630. By comparing the spectra of the period with and without the type-B QPO, we found that the main difference appears at energy bands above ∼2 keV, suggesting that the QPO emission is dominated by the hard Comptonized component. During the transition, a change in the relative contribution of the disc and Comptonized emission was observed. The disc flux decreased while the Comptonized flux increased from non-QPO to type-B QPO. However, the total flux did not change too much in the NICER band. Our results reveal that the type-B QPO is associated with a redistribution of accretion power between the disc and Comptonized emission. When the type-B QPO appears, more accretion power is dissipated into the Comptonized region than in the disc. Our spectral fits give a hint that the increased Comptonized emission may come from an additional component that is related to the base of the jet.